Breast Cancer to Meningioma: A Rare Case of Tumor-to-Tumor Metastasis - Joe, Woo Hyeong; Lee, Chang-Young; Kim, Chang-Hyun; Ko, Young San; Kim, Sang Pyo; Kwon, Sae Min (Brain tumor research and treatment, 2023)
Tumor-to-tumor metastasis (TTM) is defined as the hematogenous metastasis within a primary host tumor from a donor neoplasm. Since there is insufficient evidence regarding the pathophysiology, clinical course, and management of TTM, there are no precise guidelines for its management. A 73-year-old female patient diagnosed with breast cancer was found to have convexity meningioma. Since the size of tumor and peritumoral brain edema increased during follow-up period, the meningioma was treated with surgical resection. Postoperatively, histopathologic examination confirmed metastasis of invasive ductal carcinoma within a secretory meningioma. The final diagnosis was TTM of breast cancer in meningioma. Here, we report a rare case of intra-meningioma metastasis and a review of literature to provide a better understanding of this rare phenomenon.